Pemertahanan Bahasa Bali Aga pada Ranah Keluarga Di Desa Belantih, Kintamani, Bali - Ni Luh Yuniarti; Made Budiarsa; Ni Luh Nyoman Seri Malini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
The objective of this study is to determine the language maintenance occurring in the family domain in Belantih village, Kintamani, Bali. The analysis was limited to the language maintenance in the family domain in the form of speech and lexicons contained in Belantih Village. The data were elaborated on the analysis and presented qualitatively in the form of speech and vocabulary using the theories of the domains of language usage that proposed by Fishman (1968), the theory of language maintenance and language shifting proposed by Fishman (1972) and to determine the factors that cause the language maintenance that analyzed based on the theory strategy of language maintenance proposed by Holmes (1992). The result of the study showed that family domain is the smallest in the domains of social life, and the domain becomes an important indicator of language maintenance. BBA in the family domain in the Belantih village still usage until this time at the level of phonological which there is phoneme /a/ in the middle or at the end of the lexicon, and based on the lexical level, there are several lexicons which is the original lexicon of Belantih village. In maintenance the minority language in the middle of majority language takes some strategies such as phonological and lexical factors, the pattern of language use, demographic factors, and attitudes to the minority language, so in this case the society should have a positive attitude and a sense of belonging to the mother tongue or language minorities. This research is expected to contribute to further research related to the maintenance language as a mother tongue and not only in the domain of family but all of the domains in the society.